EFFECTS OF USING VARIOUSLY PROCESSED CULBAN GRAINS AS A PARTIAL SUBSTITUTE FOR SOYBEAN MEAL ON GROWTH OF CYPRINUS CARPIO L. - Bayan A. A.; M. A. Mohammad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The objective of this study is to improve the nutritional value of Culban Vicia peregrina using four different methods: soaking in water for 12 hours, cooking for 40 minutes, roasting for 15 minutes, and germination for 7 days to reduce the effects of anti-nutritional. For 56 days, soybean meal was utilized to replace the grains treated by the abovementioned procedures by 40% ( T3, T5 T7 and T9) and 20% (T4, T6 and T8) in the diets for common carp Cyprinus carpio L., as well as a control diet comprising 30% of soybean meal (T1). The results of the statistical analysis showed the superiority of the fed fish the T7 significantly (P≤ 0.05) in the criteria of TLW,TG and DWG. The fed fish outperformed the T4, T5 and T6 significantly in the criteria of RGR and SGR compared to the control diet(T1). The best FCR and FER were obtained in the T6 and T7, which differed significantly from the T1. With the exception of treatments T2, T7, and T9, the fed fish performed significantly better than all other treatments in the PPV criterion. It can be concluded in present study the substituting culban seeds heated or biologically(germination technique) processed could replace up to 40% of the soybean meal.